Degradation of aqueous methylparaben by non-thermal plasma combined with ZnFe2O4-rGO nanocomposites: Performance, multi-catalytic mechanism, influencing factors and degradation pathways. (May 2021) - Feng, Jingwei; Nian, Peng; Peng, Lu; Zhang, Aiyong; Sun, Yabing
Abstract: Non-thermal plasma (NTP) combined with zinc ferrite-reduced graphene oxide (ZnFe2 O4 -rGO) nanocomposites were used for the degradation of aqueous methylparaben (MeP). ZnFe2 O4 -rGO nanocomposites were prepared using the hydrothermal method, with the structure and photoelectric properties of nanocomposites then characterized. The effects of discharge power, initial MeP concentration, initial pH, and air flow rate on MeP degradation efficiency were investigated, and the multi-catalytic mechanism and MeP degradation pathways were established. Results showed that ZnFe2 O4 -rGO nanocomposites with a 10%:90% mass ratio of GO:ZnFe2 O4 had an optimal catalytic effect. The MeP degradation efficiency of NTP combined with ZnFe2 O4 -rGO (10 wt%), was approximately 25% higher than that of NTP alone. Conditions favorable for MeP degradation included higher discharge power, lower MeP concentration, neutral pH value, and higher air flow rate. The degradation of MeP by NTP combined with ZnFe2 O4 -rGO nanocomposites followed pseudo-first-order kinetics. O2 -, OH, H2 O2, and O3 were found to play important roles in the MeP degradation, as part of the multi-catalytic mechanism of NTP combined with ZnFe2 O4 -rGO nanocomposites. MeP degradation pathways were proposed based on the degradation intermediates detected by gas chromatography mass spectrometry, including demethylation, hydroxylation, carboxylation, ring-opening, and mineralization reactions. The prepared ZnFe2 O4 -rGO nanocomposites provide an approach for improved contaminant degradation efficiency, with reduced energy consumption in the NTP process. Graphical abstract: Image 1 Highlights: Synergetic degradation of methylparaben by NTP and ZnFe2 O4 -rGO was achieved. ZnFe2 O4 -rGO with a 10%:90% mass ratio of GO:ZnFe2 O4 had the best catalytic effect. O2 . -, OH, H2 O2, and O3 played important roles in the multi-catalytic mechanism. Methylparaben degradation pathway was proposed based on degradation intermediates.